Site-related streptococcal attachment to buccocervical tooth surfaces. A correlative micromorphologic and microbiologic study - Bevenius, J; Linder, L; Hultenby, K (Acta odontologica Scandinavica, 1994)
Scanning electron (SEM) microscopy of epoxy replicas made from dental impressions has shown that in buccal gingival recession the root surfaces are devoid of cementum, leaving the dentin exposed. In this study replication techniques were applied to correlate the micromorphology of the buccocervical region with early streptococcal attachment. The subjects were 27 healthy young adults. The buccocervical surfaces of all the premolars were meticulously cleaned. The subjects fasted for 2 h before impression-taking. Replicas were made from impressions in hydrophilic A-silicone, and streptococcal attachment was visualized by light microscopy of mitis-salivarius agar replicas incubated anaerobically for 48 h. The surface micromorphology was documented by SEM of corresponding epoxy replicas. Colonization only 2 h after cleaning was very sparse. Sites with healthy or inflamed gingivae had markedly different colonization patterns in the sulcular region. In 4 subjects with a total of 12 sites where gingival recession, undetected clinically, was disclosed by SEM, representative colonies were retrieved and identified microbiologically to species level. Two healthy sites per subject were also sampled. Streptococcus mutans and S. sobrinus were identified from eight sites with exposed root dentin. S. oralis predominated on the enamel surfaces. The method offers a valuable complement to in situ and in vitro microbiologic studies of exposed dentin and a novel technique for sampling clinical isolates of streptococci.